PENGARUH GERAKAN SENAM OTAK TERHADAP PERKEMBANGAN SOSIAL ANAK ADHD DI SEKOLAH BERKEBUTUHAN KHUSUS - Putu Susy Natha Astini (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2018)
ADHD have damage to the frontal limbic system with the primary symptoms are not able to focus, hyperactivity and impulsivity. Brain Gym is a collection of simple movements that can help optimize the development of the child. This study aims to determine the effect of Brain Gym Movement for Social Development of Children with ADHD at Special Needs School Denpasar City. This research was Pre Experimental with the study design The One Group Pretest Posttest Design.This research had been done from June to October 2015, at the School with Special Needs in SLBA and Youth Shine Academy. The Number of sample are 28 children ADHD with 6-12 years old, using total sampling. The data analysis using Paired t-test with a significance level of alpha = 0.05, Sig. (2 Tailed) 0,0001, thats means P value 0.05 means There is a significant influence were given of Brain Gym movements Social Development in ADHD Children with Special Needs School. It is sugested the results obtained to be used as a reference that children with ADHD were given the Brain Gym movements on a regular will help the social development of children with attention more better, controlled activity and can control impulses properly